A THEMATIC ANALYSIS OF AL-ŻANB IN QUR’AN - M. Ilham Muchtar (Hunafa: Jurnal Studia Islamika, 2018)
The Qur’an formulates al-żanb into several essences, other than as an act which can harm oneself or others. Al-żanb is also used to call sin against God and sin against fellow human beings. Al-żanb means sin, because sin is the result of an act that violates the teachings of religion and will follow the perpetrator until the Day of Judgment. The Qur’an does not mention the term al-żanb except to refer to disgraceful deeds that contain humiliation and backwardness which result in punishment in the judgment day as well as earthly sanctions. The bad influence of al-żanb in human life, both individually and socially, is enormous. Sinful acts, in addition will keep the perpetrators of their fellow human beings and their God, also gave birth to the destruction of nature and the environment. Even the occurrence of disasters on earth is inseparable from the sins committed by humans. A true and comprehensive understanding and comprehension of the nature of al-żanb, in addition to making man careful in every action, he can also learn from his mistakes so as not to make the same mistakes. Moreover, if man realizes that he can at any moment fall into sin, then it will bring a sense of tawadhu in him so that every time he ask forgiveness to Allah without waiting to have to sin first.